Impediments to the Development and Efficiency of Financial Intermediation in Brazil - Beck, Thorsten (World Bank, Washington, DC, 2015)
Reforms to improve both the level and the efficiency of financial inter-mediation in Brazil should be high on Brazilian policymakers' agendas, because of the financial sector's importance to economic growth. This means that Brazil must also improve the legal and regulatory environment in which its financial institutions operate. Brazil is weak in important components of such creditors, the enforcement of contracts, and the sharing of credit information among intermediaries. Recent reforms, such as the extension of alienacao fiduciaria to housing, the introduction of cedula de credito bancario, the legal separation of principal and interest, and improvements in credit information system, are useful steps in strengthening the framework. But more is needed. Reforms that will significantly increase the level and efficiency of financial inter-mediation, and have a positive impact on economic growth include: 1) A more efficient judicial sector and better enforcement of contracts. 2) Stronger rights for secured and unsecured creditors. 3) Stronger accounting standards and practices, to improve the quality of information available about borrowers. 4) The development of a legal and regulatory framework that facilitates the exchange among financial institutions of both negative and positive information about borrowers.